Predominance of Distinct Listeria Innocua and Listeria Monocytogenes in Recurrent Contamination Events at Dairy Processing Facilities - Irene Kaszoni-Rückerl (Microorganisms, 2020)
The genus Listeria now comprises up to now 21 recognized species and six subspecies, with L. monocytogenes and L. innocua as the most prevalent sensu stricto associated species. Reports focusing on the challenges in Listeria detection and confirmation are available, especially from food-associated environmental samples. L. innocua is more prevalent in the food processing environment (FPE) than L. monocytogenes and has been shown to have a growth advantage in selective enrichment and agar media. Until now, the adaptive nature of L. innocua in FPEs has not been fully elucidated and potential persistence in the FPE has not been observed. Therefore, the aim of this study is to characterize L. innocua (n = 139) and L. monocytogenes (n = 81) isolated from FPEs and cheese products collected at five dairy processing facilities (A−E) at geno- and phenotypic levels. Biochemical profiling was conducted for all L. monocytogenes and the majority of L. innocua (n = 124) isolates and included a rhamnose positive reaction. L. monocytogenes isolates were most frequently confirmed as PCR-serogroups 1/2a, 3a (95%). Pulsed-field gel electrophoresis (PFGE)-typing, applying the restriction enzymes AscI, revealed 33 distinct Listeria PFGE profiles with a Simpson’s Index of Diversity of 0.75. Multi-locus sequence typing (MLST) resulted in 27 STs with seven new L. innocua local STs (ST1595 to ST1601). L. innocua ST1597 and ST603 and L. monocytogenes ST121 and ST14 were the most abundant genotypes in dairy processing facilities A−E over time. Either SSI-1 (ST14) or SSI-2 (ST121, all L. innocua) were present in successfully FPE-adapted strains. We identified housekeeping genes common in Listeria isolates and L. monocytogenes genetic lineage III. Wherever there are long-term contamination events of L. monocytogenes and other Listeria species, subtyping methods are helpful tools to identify niches of high risk.